The Use of Hydroxyurea During Pregnancy in Sickle Cell Anemia Women: A Case Series and Literature Review - Silva, Flávia Anchielle Carvalho; Ferreira, Ana Laura Carneiro Gomes; Pimentel, Luisa Martins; Maciel Lyra, Carlos Henrique Monteiro; Hazin-Costa, Manuela Freire; Guerra, Glaucia Lins; Araújo, Aderson Silva; Souza, Ariani Impieri (Journal of Hematology Research, 2021)
Hydroxyurea (HU) has been an effective treatment for sickle cell anemia (SCA) by inducing fetal hemoglobin production as well as reducing the rate of painful crisis. The use of HU during pregnancy still has been a concerned situation due to the risk of malformation, but there is already a proposal for the possibility of the use, even during pregnancy, depending on the situation of the disease. On the other side, the potential of HU for mutagenesis and teratogenesis in humans has not been confirmed yet. This case series describe the perinatal outcomes on women at a Women's Care Center in Recife, Brazil. Women used HU early in their pregnancies and no record of malformation was report. Our sample was composed of 13 SCA women using HU just before or during pregnancy. Of these women, 4 had gotten pregnant twice by using HU and for this we have analyzed a total of 17 cases. There were no reports on malformation in any of these cases. In the literature review, we found seven studies on the use of HU in pregnancy and only one of these studies reported malformation in a fetus. We concluded that HU usage and teratogenic effects has not been confirmed in humans yet and suggested to await results of well-controlled studies to define the use of HU as a treatment for vasooculsive crises during pregnancy. Thus, we consider that this publication could be added to other cases in which have been already published where fetal malformation has not been registered yet.